Os discursos sobre a violência nos programas da Secretaria da Educação do Estado de São Paulo - Pino, Nadia Perez (2017)
This dissertation naimed to analyze the discourses about violence in the programs of the State Department of Education of São Paulo - SEESP - who se purpose is to avoid violence in school settings. Two questions guide dour research: Why are there so many programs created to avoid violence? In which way these programs understand violence and what are their conceptions of school, youth and society? We conducted a documentary research on the different material sand official texts for each program. The analysis of the discourses was based on the archaeological and genealogical method of Michel Foucault. We verified that the different discourses, with their statements, presented common conceptions about violence, youth and society, contradicting our initial hypothesis. However, despite the unity of the discourse on violence, the different programs did not dialogue among themselves. Were alized that statements presented the school as a victim external violence, and actions aimed at prevention are also located outside school, especially in partnerships with institutions of the Secretariat of Public Security and with the Judiciary Branch. In this way, educational activities to avoid and control violence are rarely discussed. The discourses of social vulnerability and risk are constantly being used to characterize young people who need measures of prevention, assimilation and control to avoid violence. The discourses do not address society, but rather the community that must be integrated into the school as a form of violence prevention. We did not observe in the discourses solutions aimed at the democratic management of conflicts and violence, although in the discourses democracy and citizenship are always tooken as an ideal that are desirable and that violence can avoid. We also verify that, progressively, SEESP is abandoning the discourse of prevention and violence combat in favor of discourses of conflict mediation.